The Antimicrobial Activity and the Median Lethal Dose of Thyme (Thymus vulgaris) Ethanolic Extract on Mice - Seham O. M. (Al-Mustansiriyah Journal of Pharmaceutical Sciences, 2013)
The antimicrobial activities of thyme (thymes vulgaris) ethanolic extract was studied by agar well diffusion technique against tested organisms (Esherichia coli, Staphylococcus aureus and Candida albicans). The results were showed that the extract have antibacterial and antifungal activity against tested microorganisms. The results were also showed that the median lethal dose (LD50) of ethanolic extract of thyme in laboratory mice was about (4220 mg/kg B.w). The toxic signs during 24 hours after oral administration of thyme extract were rapid breathing, dullness, contraction of abdominal muscles, paralysis then death.